Flame Propagation and Oscillation in a Millimeter-scale Constant Volume Space. Issue 10 (27th July 2021) - Su, Hang; Huo, Jiepeng; Wang, Xiaohan; Jiang, Liqiao; Song, Qianshi; Zhao, Daiqing
ABSTRACT: Flame propagation pictures of a propane/air mixture are captured by a high-speed camera in a visualized constant volume combustion chamber with a diameter of 150 mm, a parallel plate height of H = 1.45 mm, and an initial pressure of P 0  = 1.25 ~ 3.00 bar, in the range of flammable equivalence ratios. The results show that when H of the combustion chamber decreases, the range of the flammable equivalence ratios greatly decreases. As the equivalence ratio increases, the flame propagation speed first increases and then decreases. Due to the combined effects of the wall surface and heat loss, the propagation speed is maximum at a rich mixture of approximately φ  = 1.4. As the initial pressure increases, the flame propagation speed increases. The initial pressure has an enhancing effect on flame propagation in small space. At φ  = 1.5 ~ 1.6, under a suitable initial pressure, the phenomenon of periodic stagnation of flame propagation is observed. The instability in this flame propagation is caused by the combination of the wall surface, Darrieus-Landau instability, diffusive-thermal instability and Taylor instability. The Taylor instability and initial pressure play important roles in the periodic oscillation of unstable flame propagation. However, the initial pressure can change only the amplitude of the oscillation, not the frequency.